Adsorption mechanism and collapse propensities of the full-length, monomeric A beta(1-42) on the surface of a single-walled carbon nanotube: a molecular dynamics simulation study - Jana, Asis K.; Sengupta, Neelanjana (Biophysical Journal, 2012)
Though nanomaterials such as carbon nanotubes have gained recent attention in biology and medicine, there are few studies at the single-molecule level that explore their interactions with disease-causing proteins. Using atomistic molecular-dynamics simulations, we have investigated the interactions of the monomeric A beta(1-42) peptide with a single-walled carbon nanotube of small diameter. Starting with peptide-nanotube complexes that delineate the interactions of different segments of the peptide, we find rapid convergence in the peptide's adsorption behavior on the nanotube surface, manifested in its arrested movement, the convergence of peptide-nanotube contact areas and approach distances, and in increased peptide wrapping around the nanotube. In systems where the N-terminal domain is initially distal from nanotube, the adsorption phenomena are initiated by interactions arising from the central hydrophobic core, and precipitated by those arising from the N-terminal residues. Our simulations and free energy calculations together demonstrate that the presence of the nanotube increases the energetic favorability of the open state. We note that the observation of peptide localization could be leveraged for site-specific drug delivery, while the decreased propensity of collapse appears promising for altering kinetics of the peptide's self-assembly.